TANGGUNG JAWAB SOSIAL PERUSAHAAN DARI PERSPEKTIF KOMUNITAS DI KECAMATAN GILI GENTING SUMENEP - Enza Resdiana; Endang Widyastuti (Fakultas Ekonomi dan Bisnis, 2019)
Corporate social responsibility is very important to maintain the image andsustainability of the business in order to maintain cooperation with the community,besides that TJP carried out by Santos must be supported by community participation inthe development that will be carried out.The purpose of this study is to find out thecontribution of TJP Santos (Madura Offshore) Pty. Ltd. in the perspective of thecommunity group, Giligenting District, Sumenep District. The research method usedis qualitative descriptive.The results of this study indicate that the contribution of TJPSantos (Madura Offshore) Pty. Ltd. in the perspective of the community group,Giligenting District, Sumenep District. This can be indicated by four activities followedby community groups ranging from participating in decision making so that the financialassistance provided is in accordance with the needs of the community, participation inthe implementation of activities by participating in the development process undertaken,participation in monitoring and evaluation of development carried out by BISMA inoverseeing the development of assistance provided, besides that the community groupwas also active in providing information to the BISMA related to the development carriedout.